Legal Politics The Flow of Law Enforcement In Indonesia Review from The Constitutional Philosophy and Pancasila as The State Ideology - Ash-shidiqqi, Ellectrananda Anugerah (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This article discusses the flow of law enforcement in the State of Indonesia, which is used in the context of law enforcement in the State of Indonesia in terms of the country's Constitutional Philosophy, namely the 1945 Constitution of the Republic of Indonesia and also from Pancasila as the ideology of the Indonesian state. This article uses a normative legal research method, which in this article, of course, uses the primary legal source in the form of legislation, especially the Indonesian constitution, namely the 1945 Constitution of the Republic of Indonesia, and also uses the Pancasila Philosophy approach as the ideology of the Indonesian state. Law enforcement in the State of Indonesia today certainly shows that there is still the influence of the flow of legal positivism in law enforcement. However, on the other hand, law enforcement in this country does not only use legal positivism, but the Indonesian constitution regulates specifically about judicial power that the judiciary is intended To uphold law and justice, this is stated in Article 24 paragraph (1) of the 1945 Constitution of the Republic of Indonesia as the state constitution, besides looking at the philosophy of Pancasila as the ideology of the state, in the fifth precept it is stated that social justice for all people Indonesia, from these precepts, it can be seen that upholding social justice in running the state, this is of course also related to law enforcement and must prioritize social justice for all Indonesian people.